Successful Percutaneous Coronary Intervention through a Severely Bent Artificial Ascending Aorta Using the DIO Thrombus Aspiration Catheter. (19th July 2016) - Fujikake, Akinori; Komatsu, Takaaki; Taguchi, Isao
Abstract : A 66-year-old man was admitted to our institute because of chest pain. He had undergone replacement of the ascending aorta due to aortic dissection 9 years previously. We made a diagnosis of acute coronary syndrome, and coronary artery angiography was performed. Although the right coronary artery was successfully cannulated, a severe bend of the artificial aorta made it very difficult to advance the catheter into the left coronary artery. Ultimately, a DIO thrombus aspiration catheter was used to enter the left coronary artery, and a stent was implanted successfully. The DIO catheter is very useful when the selection of a guiding catheter is complicated, such as in the case of severe vessel tortuosity or a bend of the ascending aorta.